Ocular oscillations induced by shifts of the direction and depth of visual fixation - Bhidayasiri, Roongroj; Somers, Jeffrey T.; Kim, Jae I.; Ramat, Stefano; Nayak, Sagarika; Bokil, Harshad S.; Leigh, R. John (Annals of neurology, 2001)
Shifts of the point of fixation between two targets aligned on one eye that are located near and far (Müller paradigm) stimulates a combined saccadic‐vergence movement. In normal subjects, this test paradigm often induces saccadic oscillations of about 0.3 degrees at 20 to 30 Hz. We measured eye movements using the magnetic search coil technique in 2 patients recovering from viral opsoclonus‐myoclonus syndrome, comparing saccadic‐vergence responses to the Müller paradigm with conjugate saccades between distant targets. Both patients exhibited intermittent conjugate ocular oscillations of about 4 to 5 degrees amplitude at about 10 Hz. Combined saccadic‐vergence movements induced these oscillations twice as often as did conjugate saccades. One patient also exhibited disjunctive ocular oscillations at 10 Hz while sustaining fixation on the near target. The Müller paradigm provides a useful clinical and experimental technique for inducing saccadic oscillations. The probable mechanism is that pontine omnipause neurons, which normally gate saccades, are inhibited during the sustained vergence movement that follows the saccadic component of the response to the Müller paradigm. Ann Neurol 2001;49:24–28